Mecanismos bioquímicos e moleculares envolvidos em efeitos comportamentais induzidos por reserpina em ratos e C. elegans com ênfase em parâmetros oxidativos e dopaminérgicos - Reckziegel, Patrícia (2015)
Animal models as reserpine are helpful to understand the pathophysiology of several diseases with involuntary movements, as Parkinson s disease (PD), and to search efficient treatments. The present study tested the effects of reserpine on behavioral alterations induced by reserpine in rats and worms, with emphasis in oxidative and dopaminergic parameters, and the effect of the antioxidant gallic acid (GA) in reserpine-exposed rats. As result, reserpine (1mg/Kg, sc, for 3 consecutive days) increased the frequency of vacuous chewing movements (VCMs) in rats in relation to controls, and maintained this increase for at least 3 days after reserpine withdrawal. Treatment with GA (4.5 , 13.5 or 40.5 mg/kg/day, po) for 3 days reverted reserpine-induced increase in VCMs, showing protective effect. Neither reserpine nor GA changed oxidative parameters (TBARS and DCFH-DA oxidation), antioxidant levels (proteic and non-proteic thiol) and the activity of Na+,K+-ATPase (total and α-subunit) in striatum and cortex. Afterward, studies were performed with Caenorhanditis elegans due its several advantages in studies of neurodegeneration and of drugs mechanism of action. L1-larval stage C. elegans were exposed to reserpine (30 ou 60 μM) for different times. Reserpine decreased the survival, development, food intake, locomotor rate on food and dopamine (DA) levels in worms and it had effect on egg laying and defecation cycles. Morphological evaluations of dopaminergic cephalic (CEP) neurons in BY200 worms (with GFP coupled to dat-1 gene) reveled neurodegeneration by: 1) decreased fluorescence intensity, 2) decreased the number of intact neurons, and 3) increased the number of shrunken somas per worm. These effects were unrelated to reserpine s effect on dat-1 gene expression. Interestingly, the reserpine effects on locomotor rate, dopaminergic CEP neurons morphology and dat-1 gene expression were reverted after reserpine withdrawal. Furthermore, reserpine decreased the survival of vesicular monoamine transporter (VMAT) and dat-1 loss-of-function mutant worms, but no of tyrosine hydroxylase (TH, cat-2) and dopaminergic receptors (dop-1, dop-2, dop-3 e dop-4) loss-of-function mutants in relation to wild-type N2 worms. Reserpine also decreased the survival of worms pre-exposed to DA; and it activated SKN-1 detoxification pathway. Moreover, no differences were found in DAT and TH immunoreactivity in striatum of rats treated with reserpine and/or GA. The GA protective effects against reserpine-induced VCMs in rats are probably not related to its antioxidant and antiapoptotic properties or monoamine oxidase (MAO) inhibition. As conclusion, the reserpine decreases DA levels though action on VMAT, and it induces neurotoxicity/neurodegeneration due probably an increase on extracellular DA contents resulted from changes on DAT function. More studies evaluating the reserpine effect on DAT and the GA mechanism of protection are necessary.